1355 Implementation of a novel MRCPCH clinical exam preparation programme for paediatric trainees in the West Midlands Deanery. (17th August 2022) - Mbeledogu, Chukwudumebi; Layman, Shoshana; Siddiqui, Fahad; Reunis, Elke; Shelladurai, Sivakami
Abstract : Aims: Passing the MRCPCH Clinical exam is an important milestone in paediatric training, marking the transition of paediatric trainees from junior to senior training. Support for candidates varies by hospital, depending on the availability of tutors and the workload of each department. The COVID-19 pandemic led to redeployment of staff, increased workloads, and changes in the format of the MRCPCH clinical exam, switching from in-person to virtual examination. Candidates had to adapt to all these challenges simultaneously. We identified that providing additional support to candidates was critical to their preparation, maintaining their confidence, and ensuring their success, whilst also improving their welfare during this difficult period. Methods: We designed the 5-week West Midlands Paediatrics (WMP) exam preparation programme which included these core elements: Weekly consultant-led communication teaching Weekly buddy group teaching and peer mentorship Online resources: specialty lectures by Grid trainees available via YouTube IMG focused workshops and seminars To improve accessibility, all sessions were conducted online via Zoom or Microsoft TeaAll mentors were provided with a bank of cases and questions based on a weekly theme to reduce the preparation time required to facilitate sessions. Results: Following the initial implementation of the programme, feedback was collated from 24 trainees Consultant Teaching: 88% of candidates found the consultant teaching useful. Candidates appreciated getting feedback from consultants who are also clinical examiners and the opportunity to practice the exam in real time. Most candidates said having more sessions would ensure each candidate gets individual feedback following the practice sessions. Buddy Group Teaching: 80% of candidates found the buddy group teaching useful Candidates found that this provided another platform to practice and gain feedback and learn from different candidates in the groups. Candidates felt it could be improved by providing more support with issues such as work-life balance and well-being. Some trainees also reported difficulties accessing the buddy group sessions due to conflicting schedules. Teaching strategy: 92% of candidates said they would like more specialty and case-based teaching 38% of candidates would like more lecture-based teaching Candidates found the following resources most helpful: Consultant Teaching Buddy group and mentorship YouTube lectures and Video resources Pass Rate: 66% of candidates passed the MRCPCH Clinical exam following the programme. Mentor Recruitment: 88% of candidates said they would be happy to become mentors after passing their clinical exam. Candidates recommended hospital-based mentoring and mock exams as other ways to improve the preparation programme. Conclusion: The WMP exam preparation programme is a useful and valuable aid to revision for candidates preparing for their exaAs the MRCPCH clinical examinations move back to in-person sittings, adaptations may have to be made to the programme to ensure that it continues to provide support for our post-graduate learners.